The Role of Structural Capital in Achieving Creativity among Palestinian Universities Employees in West Bank - Al-Zeer, Imad; Jaradat, Nasser (The Arab Journal of Administration, 2021)
This study aimed to investigating the role of Structural Capital in achieving creativity among Palestinian universities’ employees. This study was carried out using the analytical-descriptive method. The study population consisted of the Palestinian universities’ employees in the West Bank (i.e., full time academics and administrative employees). A survey was designed to gather the data from the study sample which consisted of 357 surveyed employees from which a total of 321 surveys were retrieved (i.e., 89.9% of the study population). The study reached a number of results, the most important of which are: the structural capital is of great importance in the Palestinian universities represented in its various fields, and the field of systems and software is the most important areas of the structural capital of the university, followed by the field of regulations and instructions, and the manual of procedures and policies came in last place. The results also showed that the university has a highly accredited procedures and policies manual, while university staff emphasized low participation in policy formulation for the university in which they work. The results also pointed to the high importance of regulations and instructions within the structural capital, where universities have regulations and instructions covering all aspects of work at the university, and the distribution of regulations and instructions to all deanships and departments, and allow all employees to see them, and the results did not give high importance to strategic and operational plans Within the structural capital, the results indicate that the university has a clear organizational structure and published paper and electronic high rate, as well as an effective system of internal auditing and internal control of academic and administrative work. The results also showed that the importance of creativity indicators was high, the importance of the indicators was: the details, originality, fluency and lastly the flexibility. The researchers recommend the high administration at the Palestinian universities to Pay more attention to the structural capital reinforcement, because it was perceived by the sample to have the least effect, through enrolling the employees in participating in the polices & procedures manuals, and the strategic / operational plans making.